PENERAPAN PEMBELAJARAN PROJEK BERMAIN PERAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI UNTUK MENINGKATKAN MOTIVASI BELAJAR PADA KURIKULUM MERDEKA - Sari, Sri Wulan; Zayadi, Zayadi; Wahyuni, Vera (IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
The background of this research is when educators are still learning using lecture and assignment methods, as well as P5 activities on independent curriculum. This research aims to determine the implementation of the project play the role of Islamic religious education and character to improve motivation to learn tolerance material for class XI 10 at SMAN 1 Sungailiat. This research is a type of experimental research using PreExperimental Design with a One-Group Pretest-Posttest design model Design. The sample in this research was students of class XI 10 at SMAN 1 Sungaliat. Data collection was carried out using a questionnaire or questionnaire. The data in this research is instrument test analysis and analysis validity of the research object. The research results can be concluded by researchers that the scores obtained from the results pre-test before being given treatment, namely with an average value of 69.03 and the post-test obtained a score with an average value of 81.94. Obtained mean value The pre-test and post-test showed that there was an increase after being given it role playing project. This conclusion is also proven by the t-test hypothesis test using the paired sample test formula, a significant value of tcount > ttable, namely 13.555 > 2.045 and the Sig value. (2-tailed) of 0.000 < 0.05 then it can be said that Ho is rejected and Ha is accepted, thus it is concluded there are differences in the results of the pre-test and post-test in the experimental class.